Control technologies to prevent aerosol-based disease transmission in animal agriculture production settings: a review of established and emerging approaches - Ouyang, Hui; Wang, Lan; Sapkota, Deepak; Yang, My; Morán, José; Li, Li; Olson, Bernard A.; Schwartz, Mark; Hogan, Christopher J.; Torremorell, Montserrat (Frontiers in Veterinary Science, 2023)
Transmission of infectious agents via aerosols is an ever-present concern in animal agriculture production settings, as the aerosol route to disease transmission can lead to difficult-to-control and costly diseases, such as porcine respiratory and reproductive syndrome virus and influenza A virus. It is increasingly necessary to implement control technologies to mitigate aerosol-based disease transmission. Here, we review currently utilized and prospective future aerosol control technologies to collect and potentially inactivate pathogens in aerosols, with an emphasis on technologies that can be incorporated into mechanically driven (forced air) ventilation systems to prevent aerosol-based disease spread from facility to facility. Broadly, we find that control technologies can be grouped into three categories: (1) currently implemented technologies; (2) scaled technologies used in industrial and medical settings; and (3) emerging technologies. Category (1) solely consists of fibrous filter media, which have been demonstrated to reduce the spread of PRRSV between swine production facilities. We review the mechanisms by which filters function and are rated (minimum efficiency reporting values). Category (2) consists of electrostatic precipitators (ESPs), used industrially to collect aerosol particles in higher flow rate systems, and ultraviolet C (UV-C) systems, used in medical settings to inactivate pathogens. Finally, category (3) consists of a variety of technologies, including ionization-based systems, microwaves, and those generating reactive oxygen species, often with the goal of pathogen inactivation in aerosols. As such technologies are typically first tested through varied means at the laboratory scale, we additionally review control technology testing techniques at various stages of development, from laboratory studies to field demonstration, and in doing so, suggest uniform testing and report standards are needed. Testing standards should consider the cost-benefit of implementing the technologies applicable to the livestock species of interest. Finally, we examine economic models for implementing aerosol control technologies, defining the collected infectious particles per unit energy demand.